2020
DOI: 10.3389/fneur.2020.558858
|View full text |Cite
|
Sign up to set email alerts
|

Caliber of Intracranial Arteries as a Marker for Cerebral Small Vessel Disease

Abstract: Background: The dilation of intracranial large arteries caliber, may transfer more hemodynamic burden to the downstream brain capillaries, which, in the long run, results in cerebral small vessel disease (CSVD). This study aimed to investigate the relationship between intracranial artery calibers and small vessel disease. Methods: Patients with first-ever ischemic stroke of lacunar infarction subtype were enrolled via Nanjing Stroke Registry Program. An intracranial arterial Z-score, named the brain arterial r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In the study that did not report parent artery diameter, mean diameter of the parent artery reported by other sources was used as a proxy. All reported aneurysms in this study were in arteries whose mean diameter + standard deviation was less than 3.5 mm, 7 including the ACA, 15 the ACoA, 16 the MCA, 17 and the PCA. 18…”
Section: Resultsmentioning
confidence: 73%
“…In the study that did not report parent artery diameter, mean diameter of the parent artery reported by other sources was used as a proxy. All reported aneurysms in this study were in arteries whose mean diameter + standard deviation was less than 3.5 mm, 7 including the ACA, 15 the ACoA, 16 the MCA, 17 and the PCA. 18…”
Section: Resultsmentioning
confidence: 73%
“…High-resolution IVIM estimates from voxels mainly occupied by vessels, such as small arterials with relatively high blood flow [ 33 , 34 ], may yield high and estimates. Consequently, this could potentially result in categorizing them as outliers.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution IVIM estimates from voxels mainly occupied by vessels, such as small arterials with relatively high blood flow [33,34], may yield high 𝑓 and 𝐷 * estimates. Consequently, this could potentially result in categorizing them as outliers.…”
Section: Discussionmentioning
confidence: 99%